GAMBARAN AKTIVITAS FISIK PASIEN DENGAN HIPERTENSI : STUDI LITERATURE - Wulan Astika Putri; Nandang A Waluya; Anah Sasmita; Asep Setiawan (UPPM. Poltekkes Kemenkes Bandung, 2021)
This research is motivated by a high rate of hypertension world. According to the World Health Organization Data (WHO) in 2015 showed around 1.13 billion people in the world have hypertension. The number of people with hypertension continues to increase every year, it is estimated that in 2025 there will be 1.5 billion people affected by hypertension, and it is estimated that annually 10.44 million people die from hypertension and its complications. The high incidence of hypertension in the world, influenced by several factors one of which is lack of physical activity or sports. This study aims to determine the description of physical activity of patients with hypertension with the Systematic Literature Review method by analyzing 4 research results on physical activity in the period 2014 - 2018. The results of the analysis of the four research results show that the daily physical activity level of patients with hypertension still varies from mild to moderate namely mild levels as much as 60.78% - 84%, moderate levels 18.2% -70%, and severe levels as much as 13.6% and the suitability of the recommended physical activity with the physical activities carried out by hypertensive patients is not in accordance with the recommendations because the level of physical activity of patients with hypertension is still mild. It is recommended for nurses to increase promotive efforts by providing information and health education about the benefits of physical activity for hypertensive patients Keywords: Physical Actvity, Hypertension ABSTRAK Penelitian ini dilatar belakangi oleh angka kejadi hipertensi yang tinggi di dunia. Menurut Badan Kesehatan Dunia Data (WHO) tahun 2015 menunjukkan sekitar 1,13 Miliar orang di dunia menyandang hipertensi. Jumlah penyandang hipertensi terus meningkat setiap tahunnya, diperkirakan pada tahun 2025 akan ada 1,5 Miliar orang yang terkena hipertensi, dan diperkirakan setiap tahunnya 10,44 juta orang meninggal akibat hipertensi dan komplikasinya. Tingginya angka kejadian hipertensi di dunia, dipengaruhi beberapa faktor salah satunya adalah kurang aktivitas fisik atau olahraga. Penelitian ini bertujuan untuk mengetahui gambaran aktivitas fisik pasien dengan hipertensi dengan metode Systematic Literature Review dengan menganalisis 4 hasil penelitian mengenai aktivitas fisik dalam rentang waktu 2014 – 2018. Hasil analisis dari keempat hasil penelitian menunjukan bahwa tingkat aktivitas fisik sehari-hari pasien dengan hipertensi masih bervariasi dari ringan s.d sedang yaitu tingkat ringan sebanyak 60,78%-84%,tingkat sedang 18,2%-70%,dan tingkat berat sebanyak 13,6% dan kesesuaian aktivitas fisik yang dianjurkan dengan aktivitas fisik yang dilakukan pasien hipertensi belum sesuai anjuran dikarenakan tingkat aktivitas fisik pasien dengan hipertensi masih ringan. Direkomendasikan bagi perawat untuk meningkatkan upaya promotif dengan pemberian informasi dan pendidikan kesehatan mengenai manfaat aktivitas fisik bagi pasien hipertensi Kata kunci: Aktivitas Fisik, Hipertensi